Application of Cole‐Cole plot to study contact resistance of CNTs humidity sensor. Issue 5 (1st February 2013) - Zhao, Zhen‐Gang; Li, Chuan
Abstract : A new method to analyse the contact resistance of a carbon nanotubes (CNTs) humidity sensor is proposed. By analysing the Cole‐Cole plots of the sensor impedance, which was tested by an electrochemical workstation in different RH environments, the contact resistance could be achieved. According to this novel analytical method and the experimental data, the contact resistance of the sensor was about 5 Ω, which was much smaller than the resistance of the sensing film.